Grandfather Bowhead, tell me a story - Johnston, Aviaq (Inhabit junior., 2020)
"Bowhead whales are the longest-lived mammals on the planet, with a lifespan of over 200 years. In this heartwarming story, a grandfather bowhead recounts to his young grandchild calf all the beautiful, amazing, and surprising things he has seen in his lifetime-- all while ensuring the little calf that there is nothing more wondrous than the love a grandfather has for his grandchild. Richly illustrated and lovingly told, this book is a warm and inviting read, perfect for sharing with any little one."--